A creator of modern surgery – Johann von Mikulicz-Radecki and contemporary ophthalmologists at the University of Wroclaw at the turn of the 19th – 20th century - Niżankowska, Maria Hanna; Kalinowska, Joanna; Pacan, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The authors present the history of the life and achievements of Jan Mikulicz-Radecki as the creator of modern surgery and his own school of surgery, especially during his work at the Wroclaw University in 1890 – 1905 years. The contemporary ophthalmologists as Richard Foerster, Hermann Ludwig Cohn, Wilhelm Uhthoff and theirs famous coworkers are also presented.